Social Representations of the Environment in Press Media - Polli, Gislei Mocelin; Camargo, Brigido Vizeu (Paidéia (Ribeirão Preto), 2015)
Environmental issues are given prominence in the media and scientific circles. From the 60’s until early 2010 there were changes in the way people related to the environment, with a paradigm shift occurring regarding the environment. This study sought to identify the representational content disseminated by the press media on the environment in different periods. A qualitative survey was therefore conducted of documents, and data were obtained through texts published in a magazine with national circulation. The data were analyzed using the ALCESTE program with a Lexicographic Analysis. It was identified that the press media reflects the paradigm shifts, and publications dating from the late 60’s are compatible with the old paradigm, evolving over time, and are now compatible with the new environmental paradigm. The results indicate that currently the environment needs care in all its aspects and lack of care creates global impacts.